Upper-body testing of cross-country skiers - Bilodeau, B.; Roy, B.; Boulay, M. R. (Medicine & Science in Sports & Exercise, 1995)
Maximal oxygen uptake was evaluated twice during a competitive cross-country skiing season on a double-poling ski ergometer and running treadmill. Ski racers (M = 5; F = 5) were tested during December and March. No differences were observed at either of the test times. However, when groups were formed into those who peaked in December and those who peaked in April, the skiing treadmill showed significantly higher VO2peak measures at each peak time. A power test was also performed. Skiers who peaked in December had stable power output values across the season. However, those who peaked at the end of the season increased in power output from December to April. It was concluded that specific upper-body tests accommodated by the ski-treadmill were more related to the fitness state of cross-country skiers than test results obtained on a running treadmill. Implication. If fitness adaptations and states are to be sensitively assessed, the test has to be sport specific. Conducting tests on unrelated equipment requiring untrained movement patterns is wasted time.